Percutaneous screw fixation versus open fusion for the treatment of traumatic thoracolumbar fractures: A retrospective case series of 185 Patients with a single-level spinal column injury. (July 2022) - Neeley, Om J.; Kafka, Benjamin; Tecle, Najib El; Shi, Chen; El Ahmadieh, Tarek Y.; Sagoo, Navraj S.; Davies, Matthew; Johnson, Zachary; Caruso, James P.; Hoeft, Jennifer; Stutzman, Sonja E.; Vira, Shaleen; et al.
Highlights: Percutaneous fixation is a valuable option for the treatment of TL fractures. Hardware removal after fracture healing is an option. Fracture reduction may be easier to obtain with percutaneous fixation. Abstract: Study design: Retrospective Single-Center Review of Data at a Level 1 Trauma Center. Objective: Compare deformity correction and surgical outcomes of percutaneous instrumentation and open fusion in traumatic thoracolumbar fractures. Methods: In our retrospective study, all patients undergoing elective spine surgery for TL fractures at a Level 1 trauma center between 2000 and 2017 were reviewed. Patients who underwent percutaneous fixation were given the option of hardware removal after the fracture had healed. Results: A total of 185 patients were included in the study, with 109 treated with an open fusion, and 76 with percutaneous fixation. Twenty-five patients in the latter group had the instrumentation removed after the fracture had healed. None of them required reoperation. In the open fusion group 54.1% of patients required a decompressive laminectomy. Percutaneous fixation patients had a shorter operative time (98.3 min vs 214 min, p < 0.0001), shorter length of stay (9.8 days vs 13.5 days, p = 0.04), and less blood loss (68.4 cc vs 691 cc, p < 0.001). They also had a better correction of their traumatic kyphosis after surgery (p = 0.005). Conclusion: Percutaneous fixation is a valuable option for the treatment of TL fractures in cases without evidence of neural compression. It is still unclear whether hardware removal helps prevent adjacent segment degeneration. Percutaneous fixation could allow for better reduction of the fracture with improvement of postoperative alignment.